The Impact of Physical Activity on Neuroprotection in Neurodegenerative Diseases: A Special Focus on Parkinson’s Disease - Buczek, Aleksandra; Jakubczyk, Paulina; Bilczewska, Olga; Janik, Wiktoria; Handschuh, Marta; Helis, Justyna; Widera, Piotr; Banaś, Aleksandra; Michalik, Maciej; Bigajski, Hubert (Quality in Sport, 2024)
Aim of the study This study examines the impact of physical activity on neuroprotection in neurodegenerative diseases, focusing on Parkinson’s Disease (PD). It evaluates neuroprotective mechanisms, analyzes physical activity’s role in PD progression, assesses various exercise forms’ effectiveness on PD symptoms, and identifies research challenges and future directions. Materials and methods A comprehensive literature search was conducted across major databases, prioritizing studies from the past 15 years, particularly longitudinal studies and randomized controlled trials. The review critically evaluated neuroprotective mechanisms, exercise specificity, and effects on PD symptoms. State of knowledge Regular physical activity enhances neuroplasticity, regulates neurotrophic factors, reduces oxidative stress, and mitigates inflammation in PD patients. Various exercise forms show effectiveness in managing PD symptoms and potentially slowing disease progression. Challenges remain in optimizing interventions for individual patients and integrating physical activity into comprehensive PD management strategies. Conclusions The review highlights physical activity’s significant neuroprotective effects in PD, demonstrating its potential to manage symptoms and slow progression. Research gaps persist regarding long-term effects and personalized interventions. Future research should focus on optimizing exercise protocols, investigating synergistic effects with pharmacological treatments, and developing personalized interventions. This review supports physical activity as a valuable adjunctive therapy in PD, potentially influencing treatment paradigms in neurodegenerative disorders.